Recovery of basketball players after offensive technique training - Wang, Z. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: The shot accuracy and standardization in basketball games are closely related to the quality of the team`s scoring. The percentage of throws is fundamental to know if the basketing movement can be correctly detected and judged. In traditional basketball, players` skills are composed of specific movements. With the gradual development of these technical movements, coaches should pay more attention to each athlete so that their technical problems can be identified and worked on early. Objective: This article discusses how basketball players move, catch the ball on the court, and execute the shot to the basket. Methods: We randomly and voluntarily selected 90 basketball players by sampling. The independent variables, biomarkers, and kinetic patterns were properly cataloged and processed. The main test items included body, lower limb, and groin circumference. Finally, mathematical statistics were used to analyze the correlation of each index. The relationship between basketball players` movement posture and basic offensive techniques was analyzed. Results: In basketball, basic attack techniques in multifactorial training remarkably influences their score. The role of score recovery in basketball is significant. Conclusion: The quality of basketing action is directly related to the technical level of offensive basketball. A variety of ball training can improve the skill level of the basketball player.